Accreta centers and maternal morbidity for patients with placenta accreta spectrum disorders in California: a mixed-methods population-based study - Kimberly D. Gregory; Moshe Fridman; Samia Saeb; Naomi Greene; Lisa M. Korst (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective We evaluated whether placenta accreta spectrum (PAS) patients who delivered at accreta centers had reduced severe maternal morbidity (SMM), and we tested for the presence of racial disparity in SMM at these centers.Methods This is a mixed-methods, cross-sectional, population-based study of California hospitals with at least 200 annual delivery discharges from 2019 to 2021. Hospital discharge data from 2018 were used to assess the distribution of PAS cases in California hospitals and identify “high-volume” accreta hospitals (≥6 PAS cases). Hospitals meeting 7 predefined criteria by interview were labeled as accreta centers. Delivery discharges with PAS diagnostic codes from 2019 to 2021 were aggregated for these hospitals. Bivariate analyses were performed between patient risk factors and “performance” SMM (pSMM) (Yes/No). pSMM is a modified version of the Centers for Disease Control and Prevention SMM measure for hospital comparisons of potentially preventable SMM. We report rates of pSMM (defined without counting hysterectomy) by center status. A multiple hierarchical logistic regression model was constructed for the pSMM outcome. Observed-to-expected (O/E) ratios for pSMM were calculated to evaluate differences by race/ethnicity.Results There were 25 high-volume study hospitals, of which 17 (68%) qualified as accreta centers. Of 1791 PAS cases in California (prevalence of 0.15%), 788 delivered at the 25 hospitals and composed the study population. Centers delivered 93.4% of the percreta cases, 89.6% of increta cases, and 79.5% of the accreta cases, p = .0003. Rates of pSMM were 8.8% (n = 70) overall, (8.4% in centers and 11.0% in non-centers; p = .323). PAS patients were more likely to experience pSMM if they were delivered at non-centers (odds ratio 2.09, 95% confidence interval 0.91–4.80, p = .080). No differences in aggregate O/E ratios by race/ethnicity were identified.Conclusions PAS patients delivered at non-centers were twice as likely to experience pSMM, although this finding did not reach statistical significance. As rates of PAS increase, the development of standardized metrics to track improvement in clinical and patient-reported outcome measures appears warranted.